Composição da alta administração e a proatividade para a internacionalização de micro e pequenas empresas - Domingues, Luciana Madureira (2013)
This study aimed to analyze the relationship between the composition of senior management (open or closed) and proactivity (proactive and reactive postures) for internationalization in small and micro enterprises. Were used to measure the composition of high administration the scale already validated and Gubitta Gianechinni (2002) and to measure the position as the internationalization scale was used also to validity and Arroyabe Arranz (2009), which deals with internationalization as reactive posture and proactive. For this, we made a research was done with mixed methods, quantitative research being conducted with 41 Brazilian micro and small enterprises and qualitative research with three case studies. The results showed that: a) companies with the composition of senior management have opened higher level of proactive stance towards internationalization than firms with composition closed and that there are no differences between companies with the composition of senior management opened and closed with respect the reactive attitude towards internationalization, b) the presence of external members in top management makes the company has a broader vision of the whole and differentiated c) the reasons led these companies not to internationalize, despite its proactive stance with respect internationalization, were: company size, the cost for internationalization, the exchange, the overvaluation of the currency, the structural issue of the company; resistance to change, the need to grow and stand out internally before growing internationally; lack of government incentive , the national focus, the company's internal routine, and transportation difficulties. Taking into account the limitations of the study, it was concluded that the relationship between the composition of senior management and proactive in internationalization exists and that the more external members in senior management, the greater will be the level of proactivity company. Also, it is concluded that for companies have a higher level of reactivity internationalization composition of the high administration be opened or closed does not interfere because both companies with composition close to the composition as open, has to react to the environment where they are inserted for their own survival.